Precise resection of multiple pulmonary nodules using a three‐dimensional reconstruction model: A case report. Issue 6 (27th January 2021) - Chu, Xiang‐Peng; Chen, Zi‐Hao; Lin, Shao‐Min; Tang, Wen‐Fang; Zhang, Jia‐Tao; Lai, Yao‐Ming; Fu, Rui; Qiu, Zhen‐Bin; Lin, Jun‐Tao; Nie, Qiang; Yang, Xue‐Ning; Wu, Yi‐Long; et al.
Abstract: A 48‐year‐old woman presented to our department and chest computed tomography (CT) revealed five pulmonary nodules, two of which were in the left upper lobe of the lung and three in the superior segment of the left lower lobe., All the lesions were resected for comprehensive histological assessment in order to distinguish synchronous multiple primary lung cancers (SMPLCs) from intrapulmonary metastases. The nodules were all successfully removed by minimally invasive surgery under the guidance of three dimensional (3D) reconstruction, in order to preserve as much lung function for the patient as possible. Postoperative histopathological examination demonstrated the presence of SMPLC. The patient was discharged from hospital on postoperative day 4 without any complications. Abstract : In this case, there was a very special small pulmonary nodule in the anterior segment of the right upper lung. Using 3D reconstruction, as it was difficult to carry out a conventional pulmonary wedge resection, we determined that the nodule was located exactly between the roots of V3c and V3b+a. Therefore, we used electrocautery to strip the lung tissue along the boundary of V3c and V3b+a during the operation, and successfully removed the nodule.